Acute severe mitral regurgitation after blunt chest trauma. Issue 2 (11th December 2017) - Saric, Petar; Ravaee, Benjamin D.; Patel, Toral R.; Hoit, Brian D.
Abstract : Myocardial contusion and aortic injury are well‐known cardiac complications of blunt chest trauma, but valvular injury is rare. Traumatic valve injuries most commonly involve the aortic valve, with isolated mitral valve injury being quite rare. We report a case of acute severe mitral regurgitation due to ruptured chordae tendineae requiring surgical repair following a motor vehicle accident.